LncRNA XIST facilitates the odontogenic differentiation of dental pulp stem cells via the FUS/ZBTB16 - CHENG, Ruiqing; SUN, Honglei; QIAO, Xiaotong; CHEN, Xuefang (Journal of applied oral science, 2024)
This study aims to explore the regulatory mechanism of long noncoding RNA X inactive specific transcript (lncRNA XIST) in the odontogenic differentiation of human dental pulp stem cells (hDPSCs). hDPSCs were obtained from freshly extracted third molars and identified by flow cytometry. Odontogenic differentiation was induced in mineralized culture medium, and hDPSCs were infected with shRNA lentivirus targeting XIST or fused in sarcoma (FUS), followed by detection of alkaline phoshpatase (ALP) activity, alizarin red staining of mineralized nodules, Real-Time Quantitative Reverse Transcription PCR (qRT-PCR) quantification of XIST expression, and Western blot analysis of FUS, ZBTB16, and odontogenic differentiation markers (DSPP and DMP1). IF-FISH was performed to detect the cellular localization of XIST and FUS. RIP assay validated the XIST and FUS binding. ZBTB16 mRNA stability was tested after actinomycin D treatment. hDPSCs were infected with oe-ZBTB16 lentivirus and further treated with sh-XIST for a combined experiment. LncRNA XIST was highly expressed in hDPSCs with odontogenic differentiation. Downregulation of XIST or FUS weakened the ALP activity of hDPSCs, reduced mineralized nodules, diminished DSPP and DMP1 expressions. XIST binds to FUS to stabilize ZBTB16 mRNA and promote ZBTB16 expression. ZBTB16 overexpression partially reversed the inhibitory effect of XIST silencing on odontogenic differentiation of hDPSCs. In conclusion, XIST stabilizes ZBTB16 mRNA and promotes ZBTB16 expression by binding to FUS, thereby facilitating the odontogenic differentiation of hDPSCs.